The Key to Managing Inflation: Higher Wages - Blair Fix (Economics from the Top Down, 2023)
For the last few months, I've been diving into the economics of inflation. In this post, I'm excited to review some forgotten history. Our journey starts with a basic question: what is the key policy tool for managing the rate of inflation? According to mainstream economics, the key tool is the rate of interest. Hike this rate, economists argue, and you will cool an overheated economy, solving the problem of inflation. As you probably know, I don't think much of this idea. (Criticism here and here.) And so I've been looking for alternative theories of inflation management. After months spent in the library stacks, I'm happy to report that I've discovered some lost theory. During the mid-20th century, it seems that while most economists were jumping on the interest-rate bandwagon, a few researchers went in the opposite direction. They proposed that inflation could be treated with a dose of wage hikes. Needless to say, this alternative theory remains virtually unknown. And on its face, it seems absurd. But as I'll show, the wage-hike approach is strongly supported by evidence. Using standard economic tools, I find that rapid wage growth tends to be followed by a drop in inflation. The message? Policy makers should reverse course. Instead of greeting inflation with a dose of interest-rate hikes, governments should reach for the wage-rate lever. Hike wages as fast as possible, and you will surely reduce inflation.
Keywords: E31; J3; 330; inflation; wages